Ahad Hadith and Its Authoritativeness - Agustina, Restika; Ariani, Safrina; Maulidia, Maulidia; Mahfud, Aris (The Hadith Department, Faculty of Ushuluddin and Islamic Thought, State Islamic University of Raden Fatah Palembang., 2025)
Hadith ahad is a hadith narrated by one or several narrators but does not reach the level of Mutawatir, so its position is still debated among scholars. This research discusses the authenticity of the Ahad hadith according to the imams of the madhhab and jumhur ulama using a literature study method through the study of hadith books, works of classical scholars, and academic literature. Research findings show that Imam Abu Hanifah and Imam Ahmad bin Hanbal accept the ahad hadith as valid as evidence in all aspects of the Shari'a, including the creed, as long as it meets the validity requirements of the sanad and matan. Meanwhile, Imam Malik and Imam Syafi'i tend to use it in the realm of practice and worship, but not in matters of faith. The majority of scholars such as Al-Bukhari, Muslim, Ibn Hazm, Ibn Taimiyyah, and Ibn Qayyim also consider the ahad hadith to be valid as a legal proposition and belief. Al-Syaukani limits its use to the amaliah aspect because of its zanni nature. These differences reflect methodological variations in assessing the authority of ahad hadith in Islamic law.